Komparasi Penerapan Model Pembelajaran Aktif Tipe Pencocokan Kartu Indeks dengan Model Ceramah Terhadap Hasil Belajar Geografi di Kelas XI IPS SMA Negeri 3 Kerinci - Yeva Lenda Mahyastuti (Departement of Mathematics Education, 2022)
This study aims to find a significant difference of learning outcomes between active learning model types matching index cards and lecture method on learning outcomes geography in class XI IPS SMAN 3 Kerinci. The working hypothesis (H1) stated is